The enantiospecific synthesis of (+)-monomorine I using a 5-endo-trig cyclisation strategy - Berry, Malcolm B.; Craig, Donald; Jones, Philip S.; Rowlands, Gareth J. (Beilstein Journal of Organic Chemistry, 2007)
We have developed a general strategy for the synthesis of 2,5-syn disubstituted pyrrolidines that is based on the multi-faceted reactivity of the sulfone moiety and a 5-endo-trig cyclisation. This methodology was applied to the synthesis of indolizidine alkaloid monomorine I. Two factors were key to the success of this endeavour; the first was the choice of nitrogen protecting group whilst the second was the conditions for the final stereoselective amination step. Employing a combination of different protecting groups and an intramolecular reductive amination reaction we were able to prepare (+)-monomorine I in just 11 steps from commercially available D-norleucine in a completely stereoselective manner.